Payment behaviour among B40 households during COVID-19 as a mediator towards financial well-being - Magli, Amirah Shazana; Sabri, Mohamad Fazli; Abd. Rahim, Husniyah; Othman, Mohd Amim (Malaysian Consumer and Family Economics Association, 2022)
Households in the B40 income category who are economically disadvantaged would be much affected during COVID-19, where the Movement Control Order (MCO) has limited the economic activity of households and businesses. They may find difficulties in loan repayments during the pandemic. During the order, the use of FinTech would facilitate payments. Hence, this study aims to determine the mediation effect of payment behaviour in the influence of FinTech usage on financial well-being among 2,125 respondents from B40 households in Malaysia via multi-stage random sampling and influential factors on financial well-being were also determined in this paper. Selfadministered questionnaires were distributed at the respondents’ residences. The mediated financial well-being model was a fit model based on the R square of 28.4 per cent; thus, the research findings have practical significance. Significant factors in the model comprised of income, savings, net-worth, health, internal locus of control, financial stress and FinTech usage in the first model. In the second model, payment behaviour mediated the effect of FinTech usage on financial well-being among B40 households. The models were valid models based on the significant F statistics. Prudent payment behaviour should be practised to elevate financial well-being. Though FinTech facilitates payments, a good financial situation would not be achieved without proper payments made for loans. Debt advisory services will be sought to assist households in improving their debt repayment practices.